In vitro studies and microscopic evaluation of cryopreserved skin graft using anti-freeze peptide derived from antarctic yeast - Shuaib, Khan Muhammad (2016)
Cryopreservation techniques for tissues and organs pose challenges to clinicians and scientists throughout the years. Although cryopreservation dated back to the 19th century, it has been mainly applied for short period cooling method of preservation. Later, progress is made in the field of cryobiology for tissue and organ preservation with the availability of commercial liquefied gases (nitrogen and helium). The discovery and use of antifreeze proteins and their derivatives (AFPs) for tissue preservation are seen as potential to be developed commercially. In the present study, a process was developed to cryopreserve Sprague- Dawley (SD) rat skin grafts with antifreeze peptide, Afp1m, -helix peptide fragment derived from Glaciozyma antractica yeast. Its viability assessed by different microscopic and immunohistochemical techniques. This study also explored the cryopreservation properties and functional relationship of Afp1m by determining the cell toxicity and cell viability using Dunn's mouse (Mus dunni) skin fibroblast named as M.dunni (Clone III8C) cell line suspended in medium containing different concentrations of Afp1m (0.5, 1, 2, 5 and 10 mg/ml) and kept at -10 °C and -20 °C for 24, 48 and 72 h. To observe the toxicity and cryoprotectant effects on skin cells in vitro, cell toxicity determination and cryopreservation model were also developed to strengthen the study. Hypothesis of this study was that Afp1m is more effective for preservation of tissues, than the other conventional antifreezing agents with minimal detrimental effects of the tissue microstructure. To observe cytotoxicity of Afp1m, cells containing different Afp1m concentrations (0.5, 1, 2, 5 and 10 mg/ml) were incubated at 37 °C with 5% CO2. It showed different survival percentages (78.86 ± 10.17 % , 88.38 ± 3.19 % , 88.75 ± 7.19 % , 90.61 ± 7.11 % , 91.19 ± 4.52 % , 100.00 ± 0.0 %) cells were grown for 24 h, in media comprising different Afp1m concentrations i.e.10, 5, 2, 1, 0.5 mg/mL and positive control (10%FBS), respectively. The 5, 2, 1, and 0.5 mg/mL of Afp1m achieved significantly high (p<0.05) scores in cell viability (103.9 ± 6.56 % , 104.3 ± 5.13 % , 100.9 ± 1.71 % , 102.8 ± 1.24 % , 100.00 ± 0.0 %) at 72 h of treatment as compared to 10mg/mL which achieved 86.73 ± 6.92 % in cell viability. Retarded growth was observed in 10 mg/mL Afp1m at 24, 48 and 72 h. Growth was present but was slow than those treated with lower concentration (5, 2, 1, 0.5 mg/mL) and positive control. The cryopreservation properties of Afp1m was determined by cell viability in different concentrations (10, 5, 2, 1, 0.5 mg/mL) of Afp1m and a positive control (10%DMSO) at -10 °C and –20 °C for 24, 48 and 72 h.Tetrazolium dye MTT 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay was applied into 96 wells plate and then counted the live cells by ELISA plate reader. The cell viability was compared against the positive control (10% DMSO) and negative control (cells with 10% FBS) to evaluate the Afp1m containing cryomedia against standard cryopreservative DMSO and cells without any cryopreservative (10% FBS). High concentration of 10 mg/mL showed the highest recovered cell viability followed by 5 mg/mL at -10°C. The changes in the percentage of viability in different concentrations (10, 5, 2, 1 and 0.5 mg/mL) were increased from 82.65% to 151.45%, 87.29% to 145.93%, 68.89% to 78.37%, 65.81% to 69.81%, and 65.85% ± 59.53%. Afp1m concentrations of 5 and 10 mg/mL resulted significantly high (p<0.05) number of viable cells as compared to 2, 1, and 0.5 mg/mL who achieved lower cell viability and survival rate at -10 and -20°C. DNA damage was determined after cryopreservation of M. dunni Clone III8C cell line with the cryomedia containing different concentrations of Afp1m at - 10 and -20 °C. The number of AP sites was compared between Afp1m cryopreserved cells with positive control (10% DMSO) cryopreserved cells and H2O2 treated cells to determine the level of DNA damage. After vitrification no significant difference was observed in DNA integrity of 10, 5, and 2 mg/mL with DMSO cryopreserved cells at -10 °C at 24 h. At -20 °C, the DNA integrity was damaged (p<0.01) at concentrations of 2, 1 and 0.5 mg/mL Afp1m. The DNA damage was very much similar to the H2O2 treated cells i.e. higher AP sites were formed which may indicate irreversible damage to the cells cryopreserved at -20 °C. This study also described the damages caused by subzero temperatures (- 10 and -20°C) on tissue cryopreserved in different concentrations of Afp1m (0.5, 1, 2, 5 and 10 mg/mL) for72 h. Histological scores of three regions in cryopreserved skin grafts, i.e. epidermis, dermis and hypodermis showed highly significant differences among the different concentrations at -10 and - 20°C. Transmission electron microscopic (TEM) examination on tissues cryopreserved in 2, 5 and 10mg/mL concentrations of Afp1m showed cryodamage in the cells and tissues of the skin graft with less ultra-structural tissue alterations at -10 °C as compared to -20°C. To further support the present findings, cryopreserved skin grafts were assessed by applying four biomarkers, i.e. transforming growth factors (TGF- α), vascular endothelial growth factor (VEGF), sodium, Hydrogen Na(+) H(+) exchanger (NHE-1) and anion exchanger (AE2) to characterize their expressions in viable skin grafts. These biomarker antibodies demonstrated that different concentrations of Afp1m at -20 °C were ineffective freezing regime. The overall trends were observed in all concentrations cryopreserved at -20 °C and at lower concentrations 0.5,1 and 2mg/mL at - 10 °C showed low level of TGF α /VEGF and NHE1 /AE2 expressions as compared to the higher concentrations (5 and 10 mg/mL) at -10 °C. In conclusion, the integrity of skin graft layers, i.e. epidermis, dermis and hypodermis cryopreserved with lower concentrations of Afp1m (0.5, 1 and 2 mg/mL) or at -20 °C did not totally restored the three layers. Various changes in the microstructural morphology as well immunohistochemical reaction in epithelial layers, vascular endothelial cells in blood vessels and glandular ducts showed mild expressions. The present study attested that Afp1m is a good cryoprotective agent for the cryopreservation of skin graft. Higher Afp1m concentrations (5 and 10 mg/mL) at -10 °C found to be suitable for future in vivo study using Sprague dewily (SD) rat skin grafts. For further in vitro studies 5 mg/mL of Afp1m cryomedium can be optimized to investigate the suitability of the cryomedium to cryopreserve different tissues and organs at subzero temperatures besides the skin that have been studied in the present work.